2007
DOI: 10.1002/crat.200710935
|View full text |Cite
|
Sign up to set email alerts
|

Increased optical damage resistance of Zr:LiNbO3 crystals

Abstract: Zr: LiNbO 3 crystals has been grown. The crystal composition and phase are analyzed by X-ray diffration. The optical damage resistance ability of Zr: LiNbO 3 crystals is studied by the Sénarmont compensation method and the transmitted beam pattern distortion method. The saturated value of the birefringence change of 6 mol % Zr: LiNbO 3 crystal is 1.01×10, which is seven times smaller than that of congruent pure LiNbO 3 crystal. The results of UV-Visible and IR absorption spectra of Zr: LiNbO 3 crystals powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…From the analysis above, we found that the ZrO 2 doping threshold concentration is less than that previously reported [11,12]. A conclusion can be drawn that the ZrO 2 doping threshold concentration decreases as the ratio of [Li]/[Nb] increases.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…From the analysis above, we found that the ZrO 2 doping threshold concentration is less than that previously reported [11,12]. A conclusion can be drawn that the ZrO 2 doping threshold concentration decreases as the ratio of [Li]/[Nb] increases.…”
Section: Resultscontrasting
confidence: 43%
“…However, there still exist two drawbacks, namely the long response time and the low optical damage resistance. Therefore Fe:LiNbO 3 has been doped with optical damage resistant impurities (ODRI), such as Mg, Zn, In, Sc, Hf, and Zr [6][7][8][9][10][11][12][13][14]. As a result, fast response speed and high optical damage resistance ability (ODRA) have been achieved in ODRI-doped Fe:LiNbO 3 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…[93][94][95][96][97][98] The properties of LN doped with optical damage resistant ions were first summarized in a review paper 10 and later in a book by Volk et al 99 Recently, Kong et al 100 reviewed advances in the photorefraction of doped LN, focusing on tetra-, penta-, and hexavalent ions, including doubly-and even triply-doped crystals. They concluded that LN triply doped by Zr, Fe, and Mn shows excellent non-volatile holographic storage properties, and V and Mo single-doped LN have fast response and multi-wavelength storage characteristics.…”
Section: Other Divalent Trivalent and Tetravalent Odr Dopantsmentioning
confidence: 99%
“…44,45,47 In addition, the increase in the valence of the dopant decreases the threshold. [94][95][96][97][98] In general, the incorporation of ODR ions reduces the amount of antisite Nb Li in the lattice. In nearly stoichiometric LN crystals where the Nb Li concentration is almost zero, the threshold value of the dopant concentration can be lower than 0.2 mol.…”
Section: Other Divalent Trivalent and Tetravalent Odr Dopantsmentioning
confidence: 99%
“…The optical damage resistance of LN crystals can be improved by doping with certain divalent, trivalent, or tetravalent cations (e.g., Mg 2 , Zn 2 , In 3 , Sc 3 , Hf 4 ) above a critical amount [1]. Increased damage resistance in the visible optical range has been reported recently in tetravalent Zr- [2,3] and Sn-doped [4] LN crystals as well. Ferroelectric domain engineering with auxiliary UV light is of growing interest in damage-resistant lithium niobate [5].…”
mentioning
confidence: 99%